Transmit Power Control Analysis in V2x Communication System - Juraj Micek; Jan Kapitulik (Communications - Scientific letters of the University of Zilina, 2010)
Transmit power control is applied for reduction of transmission power to the level needed for reliable communication. The article describes problematic of transmit power control in ad-hoc V2X communication system applied in intelligent transport system environment.